Steam Integrated Educational Technology in Increasing the Efficiency of Eco pedagogical Basic Competencies in Continuous Education - Kuchkinov Abdumalik Yuldoshevich (International Journal on Integrated Education, 2022)
The content of eco-pedagogical core competencies in continuing education, the importance of improving the didactic support of improving the effectiveness of environmental education technologies in the process of environmental education for students, speaking about STEAM education, media studio, iSpring QuizMaker, development of eco-pedagogical core competencies to ensure the effectiveness of environmental education in the design of technologies for the transmission of environmental literacy, culture, economic, social processes.